Development of novel NK3 receptor antagonists with reduced environmental impact. Issue 16 (15th August 2016) - Yamamoto, Koki; Okazaki, Shiho; Ohno, Hiroaki; Matsuda, Fuko; Ohkura, Satoshi; Maeda, Kei-ichiro; Fujii, Nobutaka; Oishi, Shinya
Graphical abstract: Abstract: The neurokinin B (NKB)–neurokinin-3 receptor (NK3R) signaling positively regulates the release of gonadotropin-releasing hormone (GnRH) from the hypothalamus. The NK3R-selective antagonists may suppress the reproductive functions of mammals. For development of novel NK3R antagonists with reduced environmental toxicity, a structure–activity relationship study of an NK3R antagonist, talnetant, was carried out. Among several talnetant derivatives with labile functional groups in the natural environment, 3-mercaptoquinoline2f exhibited a comparable biological activity to that of the parent talnetant. Additionally, compound2f was converted into the disulfide3f or isothiazolone8 by air-oxidation, both of which showed no binding affinity to NK3R.